Fundamentals Of Entrepreneurship (ENT300) Business Model Canvas / Muhammad Aiman Hakimi Abdul Razak - Abdul Razak, Muhammad Aiman Hakimi (2020)
The name of my product is “Crunchyz Frutti” and my product is “Kerepek Nangka” or “Jackfruit chips”. Jackfruit (Artocarpus heteropyllus Linn ,syn Artocarpus integra Merr) under family Moraceae or locally known as “Nangka’ in Malaysia is a popular fruit tree grown as tropical fruit trees. It was grown in Malaysia as a commercial commodity or grown as mixed commodity with few other fruit types such as durian, rambutan, duku and so on in traditional village. Department of Agriculture Malaysia record about 3,123 hectare was grown in 2006 and increase the size to only 3,500 in 2009 with annual production for 27,830 metric tonnes. Our jackfruit chips is produce from fresh jackfruit that we get from Pahang. I register my “Crunchyz frutti” business on 1 June 2019 last year at Suruhanjaya Syarikat Malaysia (SSM). My main activity is producing “Jackfruit chips” and selling it to the customer. The location is in Ipoh Perak which is at No. 80, Jalan Panglima, 31590 Ipoh, Perak. The reason I choose the location is because the rent for the place is not to expensive and I also thinking this is as starting platform before I start grow up my business. Also this place will not disturb any residents around here during process of our production. The reason why I start this business is because I want to show what is unique in our country to the people in Malaysia also to other countries and I choose in concept of our local fruit that is “ Jackfruit “. At the same time, I want to help others that do not interested with jackfruits eat jackfruit in different ways. What unique about my product is, it is hard to find jackfruit chips around Malaysia such as in grocey store, shopping mall, night market and so on.